2014
DOI: 10.1007/s00442-014-3186-1
|View full text |Cite
|
Sign up to set email alerts
|

Whole-tree dynamics of non-structural carbohydrate and nitrogen pools across different seasons and in response to girdling in two temperate trees

Abstract: mobilized to maintain root activities during the growing season. Tree mortality was observed 1 year after girdling, at which time there was still an abundant NSC pool in the roots. We conclude that (1) different storage organs differ in their contribution to new tissue growth at the beginning of the growing season and that those storage organs holding higher fractions of the NSC or N pool are not necessarily those which mobilize more NSC or N; (2) tree growth may not be limited by carbon (C) availability; (3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
51
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 46 publications
8
51
1
Order By: Relevance
“…It is noteworthy that girdling may causes serious and permanent damage to the girdled plants (BOND;MIDGLEY, 2003;MEI et al, 2015), as noted in this study (Figure 2 C and D). .0 ¹ t test carried out at 5% probability among all treatments; ² t test carried out at 5% probability of among coppicing and girdling treatments; ³ Statistical test was not carried out due to the small frame of replications.…”
Section: Epicormic Shoots Inductionsupporting
confidence: 66%
See 1 more Smart Citation
“…It is noteworthy that girdling may causes serious and permanent damage to the girdled plants (BOND;MIDGLEY, 2003;MEI et al, 2015), as noted in this study (Figure 2 C and D). .0 ¹ t test carried out at 5% probability among all treatments; ² t test carried out at 5% probability of among coppicing and girdling treatments; ³ Statistical test was not carried out due to the small frame of replications.…”
Section: Epicormic Shoots Inductionsupporting
confidence: 66%
“…Similarly, the stress generated by the girdling technique may invert the translocation direction, transforming the drains in sources and influencing the conduction of photo assimilates to the region below the cut (MEI et al, 2015). It is noteworthy that girdling may causes serious and permanent damage to the girdled plants (BOND;MIDGLEY, 2003;MEI et al, 2015), as noted in this study (Figure 2 C and D).…”
Section: Epicormic Shoots Inductionsupporting
confidence: 55%
“…Barbosa and Wagner (1989) stated that the severity of the effects depended greatly on when the girdling was performed during the growth period, on the localized hormones synthesis and transport, as well as the weather conditions or the genetic predisposition of the species. Recent studies reported that the induced stress caused by girdling stopped the growth of already formed cells, proving the depletion of the soluble non-structural carbohydrates from the living cells below the girdling (Dunn and Lorio 1992;Mei et al 2015). Nevertheless, Wilson (1968) found enough carbohydrates left for cell differentiation and lignification in the already formed cells in white pine (Pinus strobus L.).…”
Section: Discussionmentioning
confidence: 99%
“…This cambial reactivation occurred during the second half of August after a drought event in both examined years (2013 and 2014). Apparently, root carbon may be mobilized for growth even several weeks after the girdling (Mei et al 2015). However, the cell differentiation below the girdling, was unquestionably carried out with a significantly lower intensity, obviously due to the reduced supply of assimilates and plant hormones (auxin and giberilin), which strongly define the cell formation and the cell wall lignification process (Tokunaga et al 2006;Sorce et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…There may also be differences in the amounts of carbon used from different storage organs e.g. NSC in shoots vs. roots (Mei et al 2015). 2) The functional structure of the tree must be maintained during a long period (Mäkelä and Valentine 2006).…”
Section: Future Improvements and Possibilities Of Cassiamentioning
confidence: 99%